Is early or late biological maturation trigger obesity? A machine learning modeling research in Turkey boys and girls - Gülü, Mehmet; Yagin, Fatma Hilal; Yapici, Hakan; Irandoust, Khadijeh; Dogan, Ali Ahmet; Taheri, Morteza; Szura, Ewa; Barasinska, Magdalena; Gabrys, Tomasz (Frontiers in Nutrition, 2023)
The primary aim of this study was to examine the relationship between biological maturation and obesity. Overall, 1328 adolescents (792 boys and 536 girls) aged 12.00 ± 0.94–12.21 ± 0.99 years, respectively (Measured for body mass, body stature, sitting stature). Body weights were deter-mined with Tanita body analysis system and adolescent obesity status was calculated according to the WHO classification. Biological maturation was determined according to the somatic maturation method. Our results showed that boys mature 3.077-fold later than girls. Obesity was an increasing effect on early maturation. It was determined that being obese, overweight and healthy-weight increased the risk of early maturation 9.80, 6.99 and 1.81-fold, respectively. The equation for our predictive model is: Logit (P) = 1 / (1+ exp (- (-31.386 + sex-boy * (1.124) + [chronological age = 10] * (-7.031) + [chronological age = 11] * (-4.338) + [chronological age = 12] * (-1.677) + age * (-2.075) + weight * 0.093 + height * (-0.141) + obesity * (-2.282) + overweight * (-1.944) + healthy weight * (-0.592)))). Logistic regression model predicted maturity with 80.7% [95% CI: 77.2%-84.1%] accuracy. In addition, the model had a high sensitivity value (81.7% [76.2%-86.6%]), which indicates that the model can successfully distinguish adolescents with early maturation. In conclusion, sex and obesity are independent predictors of maturity, and the risk of early maturation is increased, especially in the case of obesity and in girls.